Analisis Terhadap Implikasi Perseroan Terbatas Yang Didirikan Melalui Biro Jasa Hukum - Almira, Kun Salma (Officium Notarium, 2023)
A notary has the duties and authority to make a deed of establishment of a limited liability company. However, in reality, it was found that Notaries did not sign the deed of establishment simultaneously in front of the presenters. The formulation of the problem in this research is first, what are the implications of a Limited Liability Company established through a Legal Services Bureau without being signed by a Notary at the same time? Second, what is the Notary's responsibility regarding the deed of establishment of a Limited Liability Company which was established through the Legal Services Bureau without being signed by a Notary at the same time? This research is normative legal research carried out using a statutory approach and a conceptual approach. The results of the research and discussion show that the implication that occurs is that the deed of establishment of a limited liability company is degraded into a private deed. Apart from that, according to the principle of responsibility based on mistakes, notaries can be held responsible if they are proven guilty. The responsibility referred to is in the form of reimbursement of costs, compensation, and interest. This is regulated in Article 44 of Law Number 2 of 2014 on Amendments to Law Number 30 of 2004 on the Position of Notaries.Key Word: Legal Services Bureau, Notary, Limited Liability Company AbstrakNotaris memiliki tugas dan kewenangan dalam membuat akta pendirian sebuah perseroan terbatas. Namun, pada kenyataannya ditemukan Notaris yang tidak menandatangani akta pendirian secara bersamaan di hadapan para penghadap. Rumusan masalah dalam penelitian ini yaitu pertama, bagaimana implikasi Perseroan Terbatas yang Didirikan melalui Biro Jasa Hukum tanpa ditandatangani oleh Notaris secara bersamaan? Kedua, bagaimana tanggung jawab Notaris terhadap akta pendirian Perseroan Terbatas yang didirikan melalui Biro Jasa Hukum tanpa ditandatangani oleh Notaris secara bersamaan? Penelitian ini merupakan penelitian hukum normatif yang dilakukan dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian dan pembahasan menunjukkan bahwa implikasi yang terjadi ialah akta pendirian perseroan terbatas terdegrasi menjadi akta dibawah tangan. Selain itu, menurut prinsip tranggung jawab berdasarkan kesalahan Notaris dapat dimintakan pertanggung jawaban apabila terbukti bersalah. Tanggung jawab dimaksud berupa penggantian biaya, ganti rugi dan bunga. Hal tersebut diatur dalam pasal 44 Undang Undang Nomor 2 Tahun 2014 tentang Perubahan Atas Undang Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris.Kata-kata Kunci: Biro Jasa Hukum, Notary, Perseroan Terbatas